Three Eurasian malvid-associated Baridinae (Coleoptera, Curculionidae) with widely different vestiture: congeneric or not? - Prena, Jens; Liu, Ning; Ren, Li; Wang, Zhiliang; Zhang, Runzhi (Zootaxa, 2021)
Based on biological, morphological, distributional and genomic data, it is concluded that the malvid-associated Baris albosparsa (Faust), Malvaevora timida (Rossi) and Squamobaris aurea Pajni, Kohli & Kumar are monophyletic and distinct from Baris Germar. Squamobaris Pajni, Kohli & Kumar is synonymized with Malvaevora Zaslavskij (new synonymy). Baris albosparsa and S. aurea are transferred to Malvaevora (new combinations). Baris timida polita Reitter, B. subtilina Reitter, Baridius landgrebii Hochhuth and Baridius striatopunctatus Gistel are synonymized with M. timida and Baris striatopunctata Reitter is synonymized with Melanobaris carbonaria (Boheman) (new synonymies). Lectotypes are designated for B. timida polita and B. landgrebii. Baris striolala Aurivillius is recorded from China for the first time.